Meningkatkan Keterampilan Menulis Surat Dinas Dengan Metode Discovery Pada Siswa Kelas Xii IPA 4 SMA Negeri 4 Pandeglang - Sayekti Widyaningsih (Universitas Mathla'ul Anwar Banten, 2017)
This action research is aims to (1) know the official letter writing, (2) investigate the implementation discovery methods and (3) know the effect of the discovery method of writing official letters. The method used in this research is action research. since the research carried out to solve the problem of learning in a class then this reasearch also include descriptive. Based on the results of the study in the first cycle to the third cycle was found that the official letter writing skills of students has increased from the first cycle to the third cycle, namely, the first cycle (37.50%), the second cycle (27.50%), the third cycle (95.00 %). This indicated that the letter-writing agency must consider (1) the elements of language, (2) Elements of official letter are: letterhead, letter number, attachments, subject, date of mailing, the address, salutation, letter, greetings cover, signature, full name of the sender, title, and copies, (3), Content and (4) format, official letter already have a standard format which consists of opening, content and cover. Additionally discovery method stimulates the activity of students to learn independently find the constraints faced in lessons.